Characterizing e-cigarette use in veteran smokers with mental health conditions. (December 2019) - Wang, John; Rogers, Erin; Fu, Steven; Gravely, Amy; Noorbaloochi, Siamak; Sherman, Scott
Abstract: Introduction: The use of electronic cigarettes (e-cigarettes) in smokers with mental health conditions (MHC) is not well understood. Aims: This study aims to compare e-cigarette users and non-users among veteran smokers with MHC to characterize differences in smoking behavior, motivation to quit, psychological distress, primary psychiatric diagnosis, and other factors. Methods: Baseline survey data were used from a randomized smoking cessation trial enrolling smokers with MHC from four Veterans Health Administration hospitals. Participants were categorized as current, former (having ever tried an e-cigarette), or never e-cigarette users. Pearson's χ 2 and ANOVA Type-3 F -tests were used to test the bivariate associations between e-cigarette use and variables measured. Results: Among 1, 836 participants, mean age was 58 years (STD ± 12.5), 87% were male, 15% were current e-cigarette users ( n = 275), and 27% were former users ( n = 503). Sixty-five percent of e-cigarette users reported 'wanting to quit smoking' as a primary reason. Mean readiness to quit smoking (1–10) was 7.2, 6.8, and 6.4 for current, former, and never e-cigarette users, respectively ( P = 0.0002). Sixty-three percent of current and former users and 55% of never-users reported some mental distress on Kessler-6 scale ( P = 0.0003, OR = 1.4, 95% CI 1.1–1.7). A primary psychiatric diagnosis of alcohol or substance use disorder was recorded for 50% of current or former users and 60% of never-users ( P = 0.0003, OR = 0.69, 95% CI 0.56–0.84). Conclusions: E-cigarette users were more ready to quit and most often reported using e-cigarettes to assist with quitting. E-cigarette users had more psychological distress and were less likely to have substance use disorders as their primary psychiatric diagnosis.